Preventive maintenance of pyoinflammatory complications and cosmetic defects at appendectomy - S. A. Fomin (Бюллетень сибирской медицины)
It is developed and takes root slanting pararektal mini-invasive access to a dome of a blind gut at sharp appenditcite. Indications for use of mini-access are certain. The technics of performance of operation is described. For an estimation of an operational trauma the comparative analysis of changes LII, dynamics leucocites, temperature reaction of an organism, level CRB and the CIC is lead. Advantages and lacks of the offered access are revealed. It is studied microbic contaminations a belly cavity, an operational wound before processing by antiseptics. The bacteriological method leads allocation from an operational wound of microorganisms and their identification on morphological, tinktorial, fermential and to antigenic properties. Efficiency of processing of an operational wound is estimated by various antiseptics. Duration of operation appendectomy from mini-access averaged 39,5 minutes, at traditional access — 46 minutes. Time of a finding of patients in a hospital with 8,75 till 6,1 days has decreased.